Buthelezi : a Biography. - Temkin, Ben (Taylor and Francis, 2013)
Ben Temkin, Buthelezi's biographer, had the full co-operation of Chief Buthelezi in the writing of this book. There were interviews and discussions in KwaZulu and in Johannesburg, in offices, at the airport, in hotels, in private homes and even while they travelled between centres in KwaZulu.